2018
DOI: 10.1021/acsami.7b15796
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional PHPMA-Derived Polymer for Ratiometric pH Sensing, Fluorescence Imaging, and Magnetic Resonance Imaging

Abstract: In this paper, we report synthesis and characterization of a novel multimodality (MRI/fluorescence) probe for pH sensing and imaging. A multifunctional polymer was derived from poly(N-(2-hydroxypropyl)methacrylamide) (PHPMA) and integrated with a naphthalimide-based-ratiometric fluorescence probe and a gadolinium-1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid complex (Gd-DOTA complex). The polymer was characterized using UV-vis absorption spectrophotometry, fluorescence spectrofluorophotometry, magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 51 publications
(80 reference statements)
1
26
0
1
Order By: Relevance
“…It was found that 90% cell viability was observed after 24 hours of incubation with M2 at a concentration of 280 µg/mL (eight times higher than that of the normal concentration), indicating the superior biocompatibility of this nano-oxygen sensor (Figure 11). This result is compared with similar probes by Fengyu Su et al (higher than 80%) and Tingting Pan (higher than 88% with three times higher than normal concentration), suggesting that no obvious cell toxicity is observed [39,48]. It should be pointed out that these micelles did not have cell permeability during the eight-hour experimental period in which we performed cell respiration testing.…”
Section: Cell Viability Testsupporting
confidence: 75%
“…It was found that 90% cell viability was observed after 24 hours of incubation with M2 at a concentration of 280 µg/mL (eight times higher than that of the normal concentration), indicating the superior biocompatibility of this nano-oxygen sensor (Figure 11). This result is compared with similar probes by Fengyu Su et al (higher than 80%) and Tingting Pan (higher than 88% with three times higher than normal concentration), suggesting that no obvious cell toxicity is observed [39,48]. It should be pointed out that these micelles did not have cell permeability during the eight-hour experimental period in which we performed cell respiration testing.…”
Section: Cell Viability Testsupporting
confidence: 75%
“…Although inorganic nanotubes, such as carbon nanotubes, titanate nanotubes and halloysite nanotubes, are also easily manufactured and could penetrate into tissues, these materials could induce adverse health effects to endothelial cells, which can limit their uses in clinics (Li, Liu, Zhou, & Cao, 2020; Long, Xiao, Liu, & Cao, 2017; Wu et al, 2020). Previous studies also used biocompatible water‐soluble polymers, e.g., poly( N ‐(2‐hydroxypropyl)‐methacrylamide) (PHPMA), for cancer imaging and drug delivery (Su et al, 2018; Xufeng Zhou et al, 2017). However, PHPMA is a non‐degradable material, which may be not easy to be excreted from the body.…”
Section: Discussionmentioning
confidence: 99%
“…Detecting the regional pH of the tumor microenvironment via traditional ways (e.g., a pH meter or litmus test paper) is difficult because of its limited accessibility. pH-responsive polymers [ 65 ] with good biocompatibility can link the fluorescent molecules and optical quenchers to produce pH-dependent FRET compounds [ 66 , 67 ]. The MoS 2 nanosheets have a large specific surface area and abundant sulfur binding sites, thus the oligomeric or polymeric molecules can briefly functionalize them under mild conditions [ 68 , 69 ].…”
Section: Biosensorsmentioning
confidence: 99%